Effect of Papaya Leaf Solution (Carica papaya Linn) on the Hatching Percentage and Survival Rate of Dumbo Catfish Larvae (Clarias sp.) - Danang Yonarta; M. Azhari; Mochamad Syaifudin (Department of Aquaculture, 2024)
Eggs of dumbo catfish are known to stick to the substrate due to the presence of a mucus layer, which causes suboptimal oxygen supply and low hatching percentage. This indicates that the mucus layer must be lowered while also eliminating the need for a substrate during the hatching process. One of the natural ingredients that can be used for this purpose is papaya leaf containing the proteolytic enzyme papain. Therefore, this study aims to determine the effect of papaya leaf solution on the percentage of live embryos after soaking, hatching percentage, hatching time, survival rate, and abnormality percentage of dumbo catfish larvae. This research was carried out at the Basic Fisheries Laboratory, Aquaculture Study Program, Fisheries Department, Faculty of Agriculture, Sriwijaya University in August-October 2022. A Completely Randomized Design (CRD) was used, which consisted of four treatments and three repetitions. The treatment given was the soaking of eggs in papaya leaf solution with different concentrations of (P0/control), 2 g/0.96 L (P1), 4 g/0.96 L (P2), and 6 g/0.96 L (P3). The results showed that P2 was the best treatment with 100% live embryos after soaking, 94.06% hatching percentage, 20.24 hours hatching time, 92.78% survival rate, and 0.93% abnormality percentage. Based on these results, the soaking of dumbo catfish eggs on papaya leaf solution could increase the hatching percentage and survival rate.